Unionization and nonunion wage patterns: do low-wage workers gain the most? - Donohue, Susan M.; Heywood, John S. (Journal of Labor Research)
The writers discuss unionization and non-union wage patterns to investigate whether or not nonunion wage supplements are oriented toward low-wage workers. They modify earlier models to recognize that some workers may not keep their jobs following unionization, and they demonstrate that this modification produces no theoretical prediction that low-wage workers should receive larger union-induced wage supplements. They estimate the actual pattern of wage supplements by dividing the nonunion industry wage distribution into ordered wage groups, and they contend that no single group consistently receives the largest wage supplement.